Challenges faced by crop farmers: A survey of subsistent farmers in Kwara State, Nigeria - Ibrahim Ibrahim Al-Mustapha; Afeez Adekunle Ashiru (International Journal of Agricultural Science and Food Technology - Peertechz Publications, 2021)
Subsistence crop farming accounts for 70% of the total food production in Nigeria. However, it is faced with a plethora of challenges. Hence, this study assessed the challenges faced by rural subsistentc farmers in Kwara state under four thematic areas: 1. access to Agricultural loans and credit facilities, 2. availability of agricultural inputs, 3. access to a competitive market, and 4. access to information.  This qualitative survey was conducted like a one on one interview with 20 subsistent farmers between January and April 2021 in the three senatorial zones of the state. Results of the study were analyzed as frequencies and percentages. All of the farmers considered access to agricultural loans and credit facilities as well as unavailability of agricultural inputs as the main challenges and setbacks they face in their farming experience. Access to competitive markets and information was further considered as the secondary challenges encountered. This study has an overall objective of assessing the impact of the four thematic challenges associated with subsistent crop farming in Kwara state and to profer possible ways to bridge the gap in other to achieve food security in the state. The study reports the impediments of rural subsistence farming in Kwara state while the provision of agricultural credit facilities and subsidized agricultural inputs for subsistent farmers to achieve food safety and security was recommended.